The Effect Of Product Quality, Price And Coca Cola Promotion On Student Satisfaction Of the Faculty Of Law, Prima Indonesia University - Andre; Fenny Krisna Marpaung; William Paulus; Bella Agustri Leo; Grassella Hutasoit; Hendro Wijaya (Jurnal Mantik, 2021)
This research was conducted at Prima Indonesia University. The purpose of this study was to examine and analyze the effect of product quality, price and promotion of Coca Cola on student satisfaction at the Faculty of Law, University of Prima Indonesia. Satisfaction has decreased due to a decrease in product quality, prices and promotions that are not optimal. The research method uses quantitative. The population is 250 students and the sample is 150 students. The sampling technique used is random sampling. The results of the calculation of partial hypothesis testing Product Quality has a positive and significant effect on Student Satisfaction of the Faculty of Law, University of Prima Indonesia, partially Price has a positive and significant effect on Student Satisfaction of the Faculty of Law, University of Prima Indonesia.